Value Creation in the Public Service Ecosystem: An Integrative Framework. (15th March 2022) - Osborne, Stephen P.; Powell, Madeline; Cui, Tie; Strokosch, Kirsty
Abstract: This article develops the concept of the "public service ecosystem" across four levels—the institutional, service, individual, and beliefs levels . It does this by integrating service management and marketing theory with public administration and management theory . Consequently, it explores both the dimensions of value and value creation within the public service ecosystem at each level, and the interactions and inter‐relationships across these levels . It concludes with the key implications for public administration and management theory and pactice .